Implementasi Peraturan Daerah Banyuwangi Nomor 7 Tahun 2018 tentang Penyelenggaraan Kabupaten Layak Anak : Studi tentang Pemenuhan Hak Anak Kabupaten Layak Anak Klaster Perlindungan Khusus yang Mengalami Eksploitasi dan Kekerasan di Kabupaten Banyuwangi - Nuika Adisty Saindya; Sri Wilujeng; Leni Vitasari (Neolectura, 2023)
The child-friendly district policy is introduced as an example of dedication to the fulfillment of children's rights because children are seen as a sign of optimism for the nation's future and are considered to attract positive attention, so they must be protected and their rights fulfilled. In this study, the objectives to be achieved are to analyze and describe the implementation of Banyuwangi regional regulation number 7 of 2018 concerning the implementation of child-friendly districts, especially the fulfillment of children's rights in the special protection cluster in the Banyuwangi Regency. The method used in this study is a qualitative method based on Tachjan's thinking. The results of this study indicate that the implementing agent: The Banyuwangi Regency Government has implemented the child-friendly district policy, especially in the case of special protection. Although in general, the implementation of the implementor is good, on the other hand, the commitment and responsiveness of several related institutions still need to be maximized. On the program aspect: various programs have been provided by the Banyuwangi Regency Regional Government as a forum to support the design to implementation, to support these programs, there is a budget, Human Resources (HR), and facilities for the community have been cooperated by the Banyuwangi Regency Regional Government. In the target group aspect: the community has responded well to this policy and has participated. However, some still do not care and do not understand the existence of this policy, which causes them to tend to be less active. Based on this, communication in the form of socialization with the community needs to be maximized.